2020
DOI: 10.1051/0004-6361/201937185
|View full text |Cite
|
Sign up to set email alerts
|

Hidden magnetic fields of young suns

Abstract: Global magnetic fields of active solar-like stars are nowadays routinely detected with spectropolarimetric measurements and are mapped with Zeeman-Doppler imaging (ZDI). However, due to the cancellation of opposite field polarities, polarimetry captures only a tiny fraction of the magnetic flux and cannot assess the overall stellar surface magnetic field if it is dominated by a smallscale component. Analysis of Zeeman broadening in high-resolution intensity spectra can reveal these hidden complex magnetic fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
105
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(125 citation statements)
references
References 121 publications
(208 reference statements)
17
105
2
1
Order By: Relevance
“…A similar conclusion can be drawn from a study of stars with different spectral types and activity levels (See et al 2019). In that study, the estimated filling factor f using the large-scale surface magnetic field and total surface magnetic flux follows a similar power-law relation as in the work of Kochukhov et al (2020) but with δ = 0.78. In conclusion, these results of stellar observations provide further support for using Eq.…”
Section: Magnetic Field and Heating Of Coronal Plasmasupporting
confidence: 81%
See 2 more Smart Citations
“…A similar conclusion can be drawn from a study of stars with different spectral types and activity levels (See et al 2019). In that study, the estimated filling factor f using the large-scale surface magnetic field and total surface magnetic flux follows a similar power-law relation as in the work of Kochukhov et al (2020) but with δ = 0.78. In conclusion, these results of stellar observations provide further support for using Eq.…”
Section: Magnetic Field and Heating Of Coronal Plasmasupporting
confidence: 81%
“…( 7) is also roughly valid for other stars. In a study of solar-like stars, Kochukhov et al (2020) found a similar power-law relation based on the filling factor f and the averaged surface magnetic field B as f ∝ B δ with δ = 0.86 (see their Fig. 8).…”
Section: Magnetic Field and Heating Of Coronal Plasmamentioning
confidence: 63%
See 1 more Smart Citation
“…For low-mass stars, the averaged surface magnetic field measured from Stokes I is at least 10 times stronger than that measured from Stokes V (Wade et al 2000;Reiners 2012;Lehmann et al 2018;Kochukhov et al 2020), because it is not cancelled out like Stokes V. If there are magnetic spots (even of opposite polarity) on the surface, they add together to result in the Stokes I field. For an active star we can assume that the Stokes I field is entirely coming from star spots.…”
Section: Simulated Magnetic Spotsmentioning
confidence: 93%
“…Пока не ясно, как в таких условиях будет работать динамо и совместимо ли это с генерацией сильных полей. Однако не исключено, что недавние наблюдения магнитных полей на звёздах-близнецах молодого Солнца [11] можно понимать как указание на возможность именно такой работы звёздного динамо. По-видимому, такое динамо должно работать непосредственно на поверхности звезды, так что гипотетическое пятно, занимающее практически всю поверхность звезды, должно непрерывно регенерироваться механизмом динамо.…”
Section: энергетика звёздных супервспышекunclassified